Identification of Potential Key Genes Associated With the Pathogenesis, Metastasis, and Prognosis of Triple-Negative Breast Cancer on the Basis of Integrated Bioinformatics Analysis - Zhao, Bin; Xu, Yali; Zhao, Yang; Shen, Songjie; Sun, Qiang (Frontiers in Oncology, 2020)
Object: Breast cancer is the most common solid tumor affecting women and the second leading cause of cancer-related death worldwide and triple-negative breast cancer (TNBC) is the most lethal subtype of breast cancer compared with other breast cancer subtypes. We aimed to find the potential TNBC-specific therapeutic targets by performing integrative analysis on previously published TNBC transcriptome microarray data. Methods: Differentially expressed genes (DEGs) between TNBC and normal breast tissues were screened using 6 GEO datasets, and DEGs between metastatic TNBC and non-metastatic TNBC were screened using 1 GEO dataset. KEGG and GO enrichment analysis were performed on the Overlapped DEGs. TCGA TNBC data was used to identify candidate genes which were strongly associated with survival. Expression of the candidate genes in TNBC cell lines were blocked or augmented using a lentivirus system, and transwell assay were used to test its effect on TNBC migration. Results: 8 up-regulated genes and 9 down-regulated genes were found to be differentially expressed both between TNBC and normal breast tissues, and between metastatic TNBC and non-metastatic TNBC. Among them, SP100P and SDC1 were identified as risky prognostic genes. Furthermore, SDC1-over-expression TNBC cells showed enhanced migration ability, while SDC1 blockade remarkably reduced the migration of TNBC cells. Conclusion: Our study identified that S100P and SDC1 may be potential treatment targets as well as prognosis biomarkers of TNBC.